Proving coexistence of ice‐like and quartz‐like structure in localized liquid water by stimulated Raman scattering. (27th August 2019) - Wang, Shenghan; Fang, Wenhui; Li, Fabing; Wang, Ying; Yang, Bo; Lang, Hongzhi; Cao, Xianwen; Li, Zhanlong; Sun, Chenglin; Men, Zhiwei
Abstract: Liquid water is a complex system consisting of ice‐like and quartz‐like structure based on the classic two‐state model. Although lots of theoretical work have been developed about this model, the experimental evidences are still needed. Herein, a 355‐nm pulse laser is employed to excite stimulated Raman scattering (SRS) of liquid water both in bulk and on surface, with the generation of shockwave‐induced dynamic high pressure. Two characteristic features Raman peaks of both spontaneous Raman and SRS indicate the coexistence of two structures in localized water area. The ice‐like structure corresponds to ice Ih phase under the presented conditions, because the pressure dependence behavior of Raman shift agree well with the anomaly of diffusion coefficient of ice Ih phase, when the shock wave‐induced dynamic high pressure forms. Two structures show different pressure‐dependent behaviors based on the SRS results; meanwhile, the distribution of two structures is different in bulk and on surface water. Abstract : The two‐state model of liquid water is demonstrated by both spontaneous Raman spectra and stimulated Raman spectra. The ice‐like structure of liquid water belong to ice Ih by analyzing frequency shift of corresponding Raman feature under stimulated Raman scattering. The difference of hydrogen bond between bulk water and surface water is investigated by stimulated Raman spectra.